Time Series and Trend Analysis of Fatalities from Road Traffic Accident in Lagos State, Nigeria - Atubi, Augustus .O. (Richtmann Publishing, 2013)
This study examined time series and trend analysis of fatalities from road traffic accident in Lagos State, Nigeria. The datagenerated were mostly secondary data; accident records where obtained from the Nigeria Police Force and Federal RoadSafety Commission. The data were obtained for the period of thirty two (32) years. From the time series and trend analysis, itwas observed that fatalities from road traffic accidents for each of the Local Governments under study between 1970 and2001, showed that fatalities is on the decrease with the exception of Lagos Island Local Government Area over the period ofstudy. The 16 harmonics for all the Local Government Areas considered contributed above 90% of the total variance in thetime series. This means that more than 90% of road traffic accident in Lagos State could be attributed to recklessness on thepart of drivers, ignorance of highway codes, driving under the influence of alcohol, over speeding etc. based on the findings,recommendations were proffered on how to reduce the phenomenon of fatalities from traffic accidents in Lagos State.